2022
DOI: 10.1002/agr.21766
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use and willingness to adopt digital pest and disease management: Evidence from litchi growers in rural China

Abstract: This study uses a dataset covering 928 small litchi growers in southern China to investigate the determinants of farmers' willingness to adopt digital pest and disease management (DPDM), focusing on smartphone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A common drawback of IPW, AIPW, and PSM estimators is that they can only address the endogeneity issue associated with observed factors. Rural households decide to use ICTs on the basis of both observed factors (e.g., age, education experience, and household size) and unobserved heterogeneities (e.g., innate abilities and motivations) (Cai, Qi, & Yi, 2022; Min et al, 2020; Zheng & Ma, 2021). However, we are unaware of any research in this area that accounts for the selection bias arising from observed and unobserved heterogeneities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A common drawback of IPW, AIPW, and PSM estimators is that they can only address the endogeneity issue associated with observed factors. Rural households decide to use ICTs on the basis of both observed factors (e.g., age, education experience, and household size) and unobserved heterogeneities (e.g., innate abilities and motivations) (Cai, Qi, & Yi, 2022; Min et al, 2020; Zheng & Ma, 2021). However, we are unaware of any research in this area that accounts for the selection bias arising from observed and unobserved heterogeneities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Formal education attainment is found to correlate positively with the adoption of DATs, as digital technologies require knowledge-based skills and interpretation [30,32,35]. A couple of studies have found a significant impact of health status on the adoption of on-farm digital technologies [30,32]. Farming experience likewise has a positive impact on farmers' adoption.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…As such, the farmers' capacities and knowledge clearly influence their adoption decision to use DATs. Various socioeconomic factors have been incorporated into analytical models as explanatory variables [30,32,[34][35][36]. Significant socioeconomic factors identified in the reviewed papers include age, gender, education level, health status, income (including total income and percentage of agricultural income), farming experience, and cooperative membership.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
See 2 more Smart Citations